Sie sind auf Seite 1von 37

# 1

## August 16, 2010

ALI RAZA SALEEM
2008-EE-17
Section: A
Email: ars2008ee17@hotmail.com

Punjab, Pakistan

2
Preface

## These notes are my gratitude to Madam Samina, one of the best

teacher, i have in my prestigious institution. Without whom i may
not be able to write and compile these notes. These are Dierential
Equation notes, the most important tool in the eld of science and
engineering. It is very useful particularly for engineering students
because they are mostly in search of tricks or techniques to solve
problems. In these notes, the material is researched, and the cited
one.
Enjoy it.................

3
In nature, many processess are characterized in terms of derivatives and dif-
ferentials. The mathematical equations containing these derivatives and dier-
entials are called Dierenitial Equations (DEQ's). There are some methods
to solves these equations so that you can nd the original function. Dierential
equations have many applications in engineering, physics, economics, medicines
and in many other discipline.There are two main types of dierential equations
as followed:

##  Ordinary Dierential Equations:

An ordinary dierential equation ODE
1 is a dierential equation
in which the unknown function (also known as the dependent vari-
able) is a function of a single independent variable i.e . y = f (x).

For example:

dy
1.
dx = 2x +c

+ cy = 0.
2
d y
2.
dx2

where c is a constant.

##  Partial Dierential Equations:

A partial dierential equation ( PDE) is a dierential equation
in which the unknown function is a function of multiple indepen-
dent variables and the equation involves its partial derivatives, i.e .
y = f (x, t)or u = f (x, y).

For example:

σ2 u σ2 u
1.
σx2 + σy2 =0

σ2 y 2
2.
σt2 = α2 σσxy2

## Everything in this world has some purpose and identication. Similarly,

ODE has degree and order .
 Order: The highest order derivative in the equation.
 Degree:The power of the highest order derivative in the equation.

## 1 We 'll discuss only ordinary dierential equations (ODE).

4
DEQ'S Degree Order
 3
2  2

d y
dx3 + 5 ddxy2 + ex = x 2 3
3
 2  
y1 ddxy3 + 5 dy dx + x = x 3 3
 3 1
x1 ddxy3 + 5 dydx + x = e
x
1 3

2 ODE's are classied according to their order and they are further classied
according to their method of solution as following:

## Ordinary Dierential Equations ( ODE's)

1st Order 2nd Order Higher Order
Variable Separable Constant Coecient Variable Coecient By Synthetic Division
Homogeneous Homogeneous Homogeneous By Factorization
Linear Non-homogeneous Non-homogeneous
Exact

Part I
1st Order DEQ's

1 Variable Separable
If DEQ is of the type:

f (x)dx + f (y)dy = 0

## The solution will be:

ˆ ˆ
f (x)dx + f (y)dy = c

2 In these notes, solutions to ODE0 s are explained with the help of examples.

5
Example: Solve

dy
= x y2 + 1

(x + 1)
dx

⇒ y2dy
+1 =
xdx
(x+1)

## Now, Intergrating both sides;

´ dy
´ xdx
⇒ y2 +1 = (x+1)

´ dy
´  x+1−1  ´ 1

y2 +1 = x+1 dx = 1− x+1 dx

tan−1 y = x − ln(x + 1) + c

2 Homogeneous DEQ's
Such DEQ's in which each term has the same degree are called
Homogeneous DEQ's.

Consider

dy f (x, y)
=
dx g (x, y)

## Put y = Vx where V is dierentiable.

Then,

dy dV
= V+x
dx dx
and simplify!

6
Example: Solve

x2 + y2 dx + 2xydy = 0


(x2 +y2 )
⇒ dy
dx = − 2xy

⇒V + x dV
dx = − 2Vx2 = 2V

(1+3V2 )
⇒x dV
dx = − 2V

2VdV dx
⇒ 1+3V 2 = − x

´ 2VdV
´ dx
⇒ 1+3V2 =− x

## ⇒ 13 ln 1 + 3V2 = −lnx + lnc



 31
⇒ 1 + 3V2 x=c
y
Putting V= x , we get;

 31
3y2

⇒ 1+ 2 x=c
x

## 2.1 Equations Reducible to homogeneous

As,

dy f (x, y)
=
dx g (x, y)
Now, it becomes of the type followed as:

(a1 x + b1 y + c1 ) + (a2 x + b2 y + c2 ) = 0

7
Consider

l1 : (a1 x + b1 y + c1 )

l2 :(a2 x + b2 y + c2 )

(l1 ⊥ l2)
if if(l1 || l2)
a1
6= b1
a2
b2
a1
=b
a2 b2
1

## Put x = X + h and y = Y + k Put z = a1 x + b1 y

where  h and  k are constants. Just simplify!

2.1.1 if (l1⊥l2)
Example:

(−x + y − 3) dy + (x + y + 1) dx = 0
(x+y+1)
⇒ dy
dx = − (−x+y−3)

a1 b1
As,
a2 6= b2 . Therefore,

## Put x=X+h and y = Y + k, we get;

dY (X+h+Y+k+1) (X+h+Y+k+1)
dX = − (−X−h+Y+k−3) = (X−Y+h−k+3)

## For homogeneous, we have;

h + k + 1 = 0;

h − k + 3 = 0;

⇒h = −2 and k = 1

⇒ dY X+Y
dX = X−Y

## Put Y = Vx, we get;

⇒V + X dV
dX =
1+V
1−V

1+V2
⇒X dV
dX = 1−V

⇒ dV(1−V)
(1+V2 ) =
dX
X

8
Integrating both sides;

´ dV(1−V) ´ dX
⇒ (1+V2 ) = X

## ⇒tan−1 V − 21 ln 1 + V2 = lnX + lnc



q
2
⇒tan−1 YX − ln 1+ Y
X2 = lnX + lnc

## Putting this in its original form, we get;

s
  2
y−1 (y − 1)
⇒ tan−1 − ln 1+ 2 = ln (x + 2) + c
x+2 (x + 2)

## 2.1.2 if (l1 || l2)

Example

(2x + y + 1) dx + (4x + 2y − 1) dy =0

Put z = 2x + y

dz = 2dx + dy

⇒ dy = dz − 2dx

Thus,

## (z + 1) dx + (2z − 1) dy = 0 ⇒ (z + 1) dx + (2z − 1) (dz − 2dx) =0

⇒(2z − 1) dz = − (3z − 3) dx
dx (2z−1)
⇒ dz = − 3(z−1)
´ ´ (2z−1)
⇒3 dx = − (z−1) dz

⇒ 3x = zln (1 − z) − ln (1 − z) + lnc

⇒ 3x = (z − 1) ln (1 − z) + lnc

Put z = 2x + y, we get;

3x = (2x + y − 1) ln (1 − 2x − y) + lnc

9
3 Linear DEQ's
A DEQ of the form:
 
dy
+ p(x)y1 = Q(x)
dx
or
 
dx
+ p(y)x1 = Q(y)
dy

How to Solve it! First of all, we 'll nd the (I.F.)Integrating factor.Then,
multiply your equation by (I.F.). The L.H.S. of the equation becomes the deriva-
tive of the product.And the last one is to take the integral on bothe sides and

Example:

dy
+ y =ex
dx
Here we have;
´ ´
p(x)dx 1.dx
p(x) = 1 and I.F. =e =e =ex

ex dy x x x
dx + e y = e .e

d
dx (ex .y) =e2x

## Taking Integral on both sides:

´ ´ 2x
d (ex .y) = e2x dx⇒ex .y = e2 + c

Hence,

ex
y= + ce−x
2

10
3.1 Reduction to Linear DEQ's

dy
+ p(x)y = Q(x)yn
dx
where nR

## It becomes linear if n = 0 or n = 1. Suppose n 6= 0 or n 6= 1.Then divide

the above equation by yn on both sides:

y−n dy
dx + p(x).y
(1−n)
= Q(x)

Put

V = y(1−n)

We get;

−n dy
⇒ dV
dx = (1 − n)y dx

1 dV
⇒ (1−n) . dx + p(x).V = Q(x)

dV
⇒ dx + (1 − n)p(x)V = Q(x)(1 − n)

Example:

dy
+ y = xy3
dx

## It becomes linear if n = 0 or n = 1. Suppose n 6= 0 or n 6= 1.Then divide

the above equation by yn on both sides:

⇒y−3 dy
dx +y
−2
=x

Put

V = y−2

⇒ dV
dx = −2y−3 dy
dx

Then,

11
− 12 . dV
dx + V = x ⇒
dV
dx − 2V = −2x

Here we have;
´
p(x) = −2 and I.F. =e− 2dx
=e−2x

⇒ e−2x . dV
dx − 2V.e
−2x
= −2x.e−2x
−2x
⇒ d
dx (e .V) = −2x.e−2x

## Integrating both sides, we get;

´ −2x
´
⇒ d
dx (e .V) = − 2x.e−2x
´
⇒e−2x .V = −2 xe−2x dx = −2 − 12 xe−2x − 41 e−2x + c


−2x
⇒ e−2x .V = xe−2x + e 2 + c

V = x + 12 + ce2x


## Put V = y−2 . Then,

 
1 1
= x+ + ce2x
y2 2

4 Exact DEQ's
A DEQ is of the form:

## is said to be exact if and only if:

σM σN
σy = σx .

How to solve!
´
M(x, y)dx + (TermsInN(x, y)FreeOfx) = 0

12
Example:

(x + y)dx + (x − y)dy = 0

Here we have;

## ⇒M(x, y) = x+y and N(x, y) = x − y

As,

σM σN
My = σy =1 and Nx = σx =1

My =Nx
´ ´
⇒ (x + y) dx + (−y) dy = 0

Hence,

x2 y2
+ xy − =c
2 2

Example: If

My 6= Nx

## xdy − ydx = −x3 dx

My = −1 and Nx = 1
⇒ My 6= Nx

## Then you must follow the following procedure:

´
My −Nx p(x)dx
N = p(x) ⇒ I.F.=e

## Multiplying on both sides so that it becomes an exact. Moving on the

example:

My −Nx −1−1
p(x) = N = x = − x2

Here we have;

13
´ ´ 1 −2
I.F. = e p(x)dx
= e−2 x dx =e−2lnx =elnx = x12
Then, multiplying both sides, we get;

(x3 −y) dy
´ ´
x− xy2 dx + dy

x2 dx+ x2 =0⇒ x =c
´ ´
⇒ x − xy2 dx + dy = c..............3


Hence,

x2 y
+ +y =c
2 x

## Initial and Final value Problems

 →While solving 1st OrderDEQ0 s, we get one arbitrary constant. The
value of the constant can be determined by the initial condition provided
to you in the problem.

##  →While solving 2nd OrderDEQ0 s and HigherOrderDEQ0 s requires num-

4
ber of conditions equal to the Order of the DEQ.

Part II
2nd Order DEQ's

2nd Order DEQ's are the most important one because many phenomenon in
the nature and many physical systems are characterized by such equations. We
'll gradually dive in and will solve such equations with the help of marvellous
techniques.

## A (DEQ) of the form:

dn y dn−1 y dy
ao n
+a1 n−1 + .....+an−1 +an y = 0
dx dx dx

3 We ´ ´  dy 
'll consider only dy instead of because we want
´ x
(T ermsInN(x, y)F reeOf x)dy.
4

## An nth OrderDEQ must have n − InitialConditions

14
For n = 2, we get;

2
ao ddxy2 + a1 dy
dx + a2 y = 0
2
⇒ ddxy2 + a1 dy
ao dx + a2
ao y =0

Let

d a1 a2
dx = D ⇒D2 y + ao Dy + ao y =0
 
a1 a2
⇒ y D2 + ao D + ao = 0 ⇒ f (D)y = 0

## Either f (D) = 0 or y = 0. So, we take f (D) = 0

 
a1 a2
⇒ D2 + D+ =0
ao ao
.

Then we 'll nd the roots of the above equation. These roots correspond to
r1 and r2 .
It is known as Auxiliary or Characteristic equation. There are dierent
types of roots, depending upon their nature. Let r1 and r2 be the roots of
the above equation. yc denotes the solution to homogeneous equation which is
normally called ComplementarySolution.

## 1. Real and Distinct(r1, r2 ) yc = Aer1 x + Ber2 x

2. Real and Equal(r1= r2 = r) yc = (A + Bx) erx
3. Complex(α ± iβ) yc = eαx [Acosβx + Bsinβx]
4. Imaginary(±iβ) yc = Acosβx + Bsinβx

## A DEQ of the form:

2
ao ddxy2 + a1 dy
dx + a2 y = f (x)
2
f (x)
⇒ ddxy2 + aa1o . dy a2
dx + ao y = ao

## In case of such DEQ's, we have the solution of the following type:

y=yc +yp

15
 yc ⇒5 Complementary Solution/ Transient Response/ Zero-Input Response
or Natural Response of the system which you have modelled.

##  yp ⇒6 Particular Solution/ Steady State Response/ Zero-Output Response

or Forced Response.

## Case Excitation f (x)

1. eαx
2. xn
3. sinαx or cosαx
4. eαx xn
5. e sinβx or eαx cosβx
αx

## 1. Homogeneous Solution/ Complementary Solution yc can be found easily

as described above.

eαx
2. Particular Solution: yp =
f (D) ; Replace D by α and solve. If f (D)
becomes 0. Then multiply the numerator with x and dierentiate the
denominator w.r.t D. Apply the rule again and so on.

Example:

d2 y dy
2
−5 + 6y = ex
dx dx

f (x) = 0
2
⇒ ddxy2 − 5 dy
dx + 6y = 0

## 5 For stability of the system, we check the roots of the y .

c
6 It is a function of both the system and the excitation(Input) but independent of the initial
conditions.

16
Put

d
dx = D⇒ D2 y − 5Dy + 6y = 0⇒ (D2 − 5D + 6)y = 0

⇒ f (D)y = 0

Either

f (D) = 0 or y = 0
So, we take;f (D) = 0.

⇒D2 − 5D + 6 = 0

We get;

D = 3, 2

i.e. r1 = 3 and r 2 = 2.

∴ yc =Ae3x + Be2x

## Particular Solution (yp )

f (x) ex ex
⇒yp = f (D) = f (D) = D2 −5D+6
Replace D by (α = 1), we get;

ex ex
⇒ yp = 12 −5(1)+6 = 2

Then,

y = yc + yp

Since,

ex
∴ y =Ae3x + Be2x +
2

17
If f (x) = xn where n=0 or nZ+

## 1. Homogeneous Solution/ Complementary Solution yc can be found easily

as described above.

xn n −1
2. Particular Solution: yp = f (D) = x [f (D)] , Then apply the Binomial
Series Expansion , expand it upto n − terms and simplify!

Example:

d2 y dy
2
−2 + y = x2 + 2x − 4
dx dx
There are two parts of solution:

## Complementary Solution (yc )

For that we 'll put:f (x) =0
d2 y
⇒ dx2 − 2 dy
dx + y = 0

Put

d
dx = D⇒ D2 y − 2Dy + y = 0⇒ (D2 − 2D + 1)y = 0

⇒ f (D)y = 0

Either

f (D) = 0 or y=0

So, we take

f (D) = 0

⇒ D2 − 2D + 1 = 0
2
⇒ (D − 1) = 0

We get;

⇒ D = 1, 1

i.e. r = r1 = r2 = 1

∴ yc = (A + Bx) ex

18
Particular Solution (yp )
f (x)
⇒ yp = f (D)

2
⇒ Dx2 −2D+1
+2x−4
= x2 + 2x − 4 .(1 − D)−2


## Applying Binomial Expansion, we get;

  (−2)(−D) (−2)(−2−1)(−D)2

7
⇒ x2 + 2x − 4 .(1 − D)−2 = x2 + 2x − 4 . 1 +

1! + 2! .................

  6D2

⇒ x2 + 2x − 4 . 1 + 2D
1! + 2! =
 2  
x + 2x − 4 + 2D x + 2x − 4 + 3D2 x2 + 2x − 4
2

## =x2 + 2x − 4 + 2 (2x + 2) + 3(2) = x2 + 6x + 6

Thus,
∴ yp = x2 + 6x + 6

Then,

y = yc + yp = (A + Bx) ex + x2 + 6x + 6

## 1. Homogeneous Solution/ Complementary Solution yc can be found easily

as described above.

sinαx cosαx 2

2. Particular Solution: yp =
f (D) or f (D) ; Replace D by −α2 . If f (D)
becomes 0, case fails. Then multiply the numerator with x and dieren-
tiate the denominator w.r.t. D. Apply the rule again and so on.

## 7 As the degree of polynomial (x2 + 2x − 4) is 2 so we 'll expand (1 − D)−2 upto D2 .

19
Example:

d2 y
+ y = cosx
dx2
There are two parts of solution:

## For that we 'll put:

f (x) = 0
d2 y
⇒ dx2 +y =0

Put

d
dx = D⇒ D2 y + y = 0 ⇒ y(D2 + 1) = 0

⇒ f (D)y = 0

Either

f (D) = 0 or y=0

So, we take

f (D) = 0

D2 + 1 = 0 ⇒ D2 = −1 ⇒ D = ±i

## i.e., r1 = i and r2 = −i.

Here

β=1

So,

∴ yc = Acosx + Bsinx

## Particular Solution (yp )

f (x) cosx
⇒yp = f (D) = D2 +1

## Replace D2 by (−α2 )= (−12 )= −1.

We get;

20
cosx cosx
⇒ D2 +1 = −1+1 =∞

we get:

xcosx xcosx
⇒ 2D = 2D2 .D

## Applying rule again, we get:

xcosx xcosx.D
⇒ 2D2 .D = 2(−12 ) = − x2 D(cosx)

## ⇒ − x2 D(cosx) = − x2 .(−sinx) = x2 sinx.................8

x
∴ yp = sinx
2

Then,

x
y = yc + yp = yc = Acosx + Bsinx + sinx
2

## 1. Homogeneous Solution/ Complementary Solution yc can be found easily

as described above.

eαx xn
2. Particular Solution: yp = f (D) ; Replace D by (D + α), we get;
αx n αx n
e x e x αx n −1
⇒ f (D) = f (D+α) = e x [f (D + α)] . Apply Binomial Series Ex-
n
pansion , expand it upto n − terms and operate on x !

Example:

d2 y dy
−5 = xe5x
dx2 dx
There are two parts of solutions:

We 'll dierentiate cosx only. If it would be sinx the same thing will be done.

21
Complementary Solution (yc )

## For that we 'll put:

2
f (x) = 0 ⇒ ddxy2 − 5 dy
dx = 0

Put

d
dx = D⇒ D2 y − 5Dy = 0 ⇒ y(D2 − 5D) = 0

⇒ f (D)y = 0

Either

f (D) = 0 or y=0

So, we take;

f (D) = 0

⇒ D2 − 5D = 0 ⇒ D(D − 5) = 0

We get;

D = 0, 5

i.e., r1 = 0 and r2 = 5.

∴ yc = A + Be5x

## Particular Solution (yp )

f (x) 5x x
⇒ yp = f (D) =e D2 −5D

Replace D by (D + α) = (D + 5).
Then,

5x
x x x x
⇒ e5x D2 −5D = e5x (D+5)2 −5(D+5) =e5x D2 +5D =e5x 5D = e5D . x
(1+ D5 ) (1+ D5 )

e5x x e5x D −1

⇒ 5D . (1+ D ) = 5D x 1+ 5
5

22
D −1

As the degree of polynomial x is 1. Then we 'll expand 1+ 5 upto one
term only!

5x
D −1 5x
e5x
⇒ e5D .x 1 + = e5D .x 1 + (−1) D D
  
5 5 = 5D .x 1− 5

## Now, we 'll operate on x, we get;

1
´
∵ D = dx

 
e5x e5x e5x x2 e5x x2 xe5x
x − D x5 = 1 x
 
⇒ 5D 5D . x− 5 = 5 . 2 − 5 = 10 − 25

e5x x2 xe5x
∴ yp = −
10 25
Then,

e5x x2 xe5x
y = yc + yp = A + Be5x + −
10 25

## 1. Homogeneous Solution/ Complementary Solution yc can be found easily

as described above.
αx αx
2. Particular Solution: yp = e f (D)
sinβx
or
e cosβx
f (D) ; Replace D by (D + α).

Then, replacing D2 by −β 2 . Just Simplify!

23
Example:

d2 y dy
+6 + 73y = 80ex cos4x
dx2 dx
There are two parts of solution:

## For that we 'll put:

d2 y
f (x) = 0 ⇒ dx2 + 6 dy
dx + 73y = 0

Put

d
dx = D⇒ D2 y + 6Dy + 73y = 0 ⇒ y(D2 + 6D + 73) = 0

⇒ f (D)y = 0

Either

f (D) = 0 or y = 0.

So, we take;

f (D) = 0

⇒ D2 + 6D + 73 = 0
√ √
−6± 255i 255
⇒D= 2 = −3 ± 2 i = α ± iβ

√ √ !
255 255
∴ yc = e−3x Acos( )x + Bsin( )x
2 2

## Particular Solution (yp )

f (x) 80ex cos4x
⇒ yp = f (D) = D2 +6D+73

## Replace D by (D + α) = (D + 1), we get;

x
80ex cos4x 80ex cos4x
⇒ D80e cos4x
2 +6D+73 = (D+1)2 +6(D+1)+73 = D2 +8D+80


Now, replacing D2 by −β 2 = (−42 ) = −16. We get;

## 80ex cos4x 80ex cos4x x

⇒ D2 +8D+80 = −16+8D+80 = 80e cos4x
8(D+8)

24
Rationalizing by (D − 8), we get;

x
80e cos4x (D−8)x 10ex cos4x(D−8)
⇒ 80e cos4x
8(D+8) = 8(D+8) . (D−8) = D2 −64


Replacing D2 by −β 2 = (−42 ) = −16. We get;
x x x
⇒ 10e cos4x(D−8)
D2 −8 = 10e cos4x(D−8)
−16−64 = 10e cos4x(D−8)
−80 = − 18 ex cos4x(D − 8)
Now, operating on cos4x, we get;

ex
− 18 ex cos4x(D − 8) = − 18 ex [−4sin4x − 8cos4x] = 1

2 sin4x + ex cos4x = ex 2 sin4x + cos4x

 
1
∴ yp = ex sin4x + cos4x
2

Then,

√ √ !  
−3x 255 255 x 1
y = yc + yp =e Acos( )x + Bsin( )x + e sin4x + cos4x
2 2 2

9
Variation of Parameters
There is another method to solve 2nd Order non-homogeneous DEQ0 s.The pro-
cedure to solve such type of DEQ's of the form:

2
ao ddxy2 + a1 dy
dx + a2 y = f (x)

2
f (x)
⇒ ddxy2 + a1 dy a2
ao . dx + ao y= ao

## Solution will be of the form:

y = u1 v1 + u2 v2

## Solve the associated homogeneous equation:

⇒ D2 + a1 D + a2 = 0

25
Let

## u1 = er1 x and u2 = er2 x

u1 u2 p p
Apply: D =
up up = u1 u2 − u2 u1

´ u2 (x)f (x)
1 2
For v1 : v1 = − dx
´ u1 (x)f D
For v2 : v2 =
(x)
D dx
Thus, y = u1 v1 + u2 v2

Example:

d2 y dy
2
+2 − 3y = 6
dx dx
Solution will be of the form:

y = u1 v1 + u2 v2

Solve the associated homogeneous equation and for that we 'll put:

f (x) = 0

d2 y dy
⇒ 2
+2 − 3y = 0
dx dx
Put

d
dx = D⇒ D2 y + 2Dy − 3y = 0⇒ (D2 + 2D − 3)y = 0

⇒ f (D)y = 0

Either

f (D) = 0 or y = 0
So, we take

⇒f (D) = 0

D2 + 2D − 3 = 0⇒ D = −3, 1

i.e., r1 = −3 and r2 = 1
Let

## u1 = er1 x = e−3x and u2 = er2 x = ex

26
Apply:

e−3x

ex
D = = e−2x + 3e−2x = 4e−2x
−3e−3x ex

For v1 :
´ ex 6
´ 3x 3x
v1 = − 4e−2x dx = − 23 e3x dx = − 32 . e3 + c1 = − e2 + c1

For v2 :
´ e−3x 6
´ −x
v2 = 4e−2x dx = 3
2 e−x dx = 32 . e−1 + c2 = − 32 e−x + c2

Then,

 3x 
y = u1 v1 + u2 v2 = e−3x − e2 + c1 + ex − 32 e−x + c2 = −2 + c1 e−3x + c2 ex


Thus,

∴ y = −2 + c1 e−3x + c2 ex

Part III
Higher Order DEQ's

## The methods of solving DEQ's can also be extended to equations of

10 higher
11
order DEQ's . The characteristic or homogeneous algebraic equation asso-
ciated with the DEQ:

n n−1
ao ddxyn + a1 ddxn−1y + ....... + an−1 dy
dx + an y = 0

dn y a1 dn−1 y an−1 dy an
⇒ dxn + ao dxn−1 + ....... + ao dx + ao y =0

is
 
d a1 an−1 an
dx = D ⇒ Dn + a0 D
n−1
+ ....... + ao D + ao y=0
 
a1 an−1 an
Dn + a0 D
n−1
+ ....... + ao D + ao =0

10 Higher Order non-homogeneous DEQ's can be solved in the same way as we did for the
2nd OrderDEQ0 s but it would be tedious.
11 Higher Order DEQ's are mostly solved with the help of LaplaceTransform.

27
Let r1 , r2 , .......rn be the roots of the above equation. The same technique,
we 'll apply here as in the above cases which have discussed.

Example:

d4 y d3 y d2 y dy
4
−3 3 +3 2 − =0
dx dx dx dx
Put,

d
dx = D ⇒ (D4 − 3D3 + 3D2 − D)y = 0

## The roots of the characteristic equation are:

r1 = 0 and r2 = r3 = r4 = 1

## ⇒ya = C1 er1 x = C1 e0x = C1


⇒ yb = C2 + C3 x + C4 x2 ex

Hence,

y = ya + yb = C1 + C2 + C3 x + C4 x2 ex


Part IV
Applications

Orthogonal Trajactories
In Physics or Geometry, we have to nd a family of curves that intersect a
given family of curves at right angles. Thus, it becomes crucial to nd these
trajactories.

28
Example:

y = cx2
First we 'll nd the tangent to that curve;

d y d

dx x2 = dx (c)
p 2
⇒ y .x x−2xy
4 =0
2y
⇒ yp = x

x1
y1p = − 2y 1
⇒ y1p 2y1 = −x1

## Now, Integrate to get whole family of curves:

x21
y12 + = c1
2
Hence, above ellipses are the orthogonal trajactories of parabolas y = cx2 .

29
Growth and Decay problems
Let N(t) be the amount of substance or population either growing / or
decaying. Suppose N(t) is dierentiable. Then, rate of change of N(t)is
directly proportional to the amount present.

d
N(t) ∝ N(t)
dt

## ⇒ N(t) = cekt where c = N(InitialCondition) Example:In a culture, bac-

teria increases at the rate proportional to the number of bacteria present. If
bacteria are 100 initially and are doubled in 2 hours, nd the number of bacteria
present 4 hours later. (CollegeMathematics)
As,

Initially means:

## Taking Natural logarithm on both sides, we get;

⇒ ln2 = 2k ⇒ k = 21 ln2

## Put it in (a), we get;

t
⇒ N(t) = 100e 2 ln2

## After 4 hours, we get;

4 2
⇒N(t) = 100e 2 ln2 =100eln(2) = 100(4) = 400.

30
12 Law of Cooling and Temperature Problems

It states that the time rate of change of temperature is directly proportional
to dierence in ”Body” and ”Surrounding” or ”Ambient” temperature.

d
⇒ T ∝ (T − TS )
dt
where T > TS and TS is constant

d
⇒ dt T = k (T − TS )
dT
⇒ (T−T S)
= kdt

´ dT
´
⇒ (T−TS ) = kdt

## ⇒ ln |T − TS | = kt + c ⇒ T − Ts = ekt+c = ec .ekt = cekt

⇒ T = TS + cekt

For t = 0, we get;

⇒ To = TS + c ⇒ c = To − TS

## T(t) = TS + (To − Ts )ekt

where To = InitialTemperature

## Example:A body at a temperature of 50o F is placed in an oven whose

temperature is kept at 150o F. If after 10minutes the temperature of the
o
body is 75 F, then nd the time required for the body to reach a temperature
of 100o F.

## Initial temperature of body =To = 50o F

Surrounding temperature =TS = 150o F
As,

12 This method is used by detectives who investigate at what time person has been mur-
dered or died.

31
d
⇒ T = k (T − 150)
dt
dT
⇒ (T−150) = kdt

´ dT
´
⇒ (T−150) = kdt

## ⇒ ln |T − 150| = kt + c ⇒ T − 150 = e−kt+c = ec .ekt = cekt

⇒ T = 150 + cekt

For t = 0, we get;

⇒ To = TS + c
⇒50 = 150 + c ⇒ c = 50 − 150 = −100

2 = e−0.0287t

## Taking Natural Logarithm on both sides, we get;

⇒ ln (0.5) = −0.0287t
Hence,

⇒ t = 24.75mins

32
Circuit Order Network Equation Circuits

RC 1 dVC
dt + VC
RC = E(t)
RC

RL 1 dI
dt + R
LI = E(t)
L

RLC 2 d2 I
dt2 + R dI
L . dt + I
LC = E0 (t)
L

## 13 Electric Circuit Problems

14

ODEQ's are widely used in the eld of engineering and mathematics. These
equations do marvellous jobs and keep account of the changes occuring due to
the versatile nature of derivatives and dierentials.

## Example: Consider an RC-circuit containing resistance 10Ω and

capacitance of 10−1 F. The input voltage is 5V . The initial voltage of
capacitor is zero. Find the voltage of the capacitor at any time t.

As,

dVC VC E(t)
⇒ + =
dt RC RC

## Putting R = 10Ω and C = 10−1 F.

We get;

13 RC and RL circuits,1st OrderSystems, are similar in the way they are solved.
14 RLC circuits are 2nd Order Systems i.e. these circuits are modelled as 2nd Order
DEQ0 s which can be solved as described in PART II Non-Homogeneous DEQ's.

33
dVC VC E(t)
⇒ dt + 10.10−1 = 10.10−1
dVC
⇒ dt + VC = 5
Here we have;
´ ´
p(t)dt 1.dt
⇒ p(t) = 1 and I.F. = e =e = et

## Now, multiplying with I.F. on both sides, we have;

⇒ et dV t
dt + VC .e = 5e
C t

d

⇒ dt VC .et = 5et
Now, integrating both sides, we get;

´ d
 ´
⇒ dt VC .et = 5et
t
⇒ VC .et = 5 e1 + c
⇒ VC = 5 + ce−t

Since,

## Putting values, we get;

⇒ 0 = 5 + ce−0.t
⇒ c = −5
Thus,

⇒ VC = 5 − 5e−t = 5 1 − e−t


Approximation Techniques
In mathematics, there are some situations where we cannot realize physical
systems. On the other hand, we have some techniques to approximation such
systems.

 Power Series
15

 Numerical Methods
15 Only Power Series is discussed.

34
Series Solution of DEQ's

## ⇒ y00 + b1 (x) 0 bo (x) g(x) 16

b2 (x) y + b2 (x) y = b2 (x) .................

## where p (x) and q (x) must be

17 analytic.

Example:

y0 − y = 0................(1)

Here we have;

Let

X
y= am xm
m=0

## is a solution of equation (1).

Putting values of y0 and y in (1), we get;

X ∞
X
⇒ y0 − y = mam xm−1 − am xm = 0
m=1 m=0

 

## 16 The coecent of y00 must be 1

Or A function
17 A function is said to be analytic if it is dierentiable at each point of domain
is said to be analytic if it can be expressed in a series (nite or innite) with non-negative
increasing power of x.

35
Equating coecients, we get;

xo ⇒ a1 − ao = 0

x1 ⇒ 2a2 − a1 = 0

x3 ⇒ 3a3 − a2 = 0

x4 ⇒4a4 − a3 = 0

x5 ⇒5a1 −a4 = 0

## By solving and putting values in the above equation, we get;

x2 x3
= ao + ao x + ao + ao + ...... + .........
2! 3!

x2 x3
 
= ao 1 + x + + + ...... + ......... = ao ex
2! 3!

36
If these techniques are in your hand, you can solve such problems.
And the last thing that i have to say is practise! because this is the
only thing which will lead you from better to the best.

37